Option pricing using Monte Carlo methods - Waldeckerová, Naďa (2015)
This thesis aims to analyse different Monte Carlo methods when applied to the problem of option pricing. Closer attention is paid to three variance reduction techniques, namely control variathes, importance sampling and antithetic variables, and two different approaches, least-squares Monte Carlo and quasi-Monte Carlo methods. The detailed analysis of the differences and improvements is done on a problem of plain vanilla option pricing. At the end the methods are each applied to valuation of different exotic options.